THE EFFECT OF THE DRUG MIOSTA H® IN THE TREATMENT OF PURULENT AND NON-PURULENT INFLAMMATORY PROCESSES IN THE JOINTS OF THE LEGS IN HORSES - Kh.B., Niyazov; Ruziboev, A.K.; c, Kh.H.; S.B. Abdiev; B. Kokilov; A. Ruziev (Journal of Medical Genetics and Clinical Biology, 2024)
In this article, when treating horses with a purulent coffin joint, surgical treatment is performed, enrofloxacin 10% is injected into the muscle, platelet autoserum is injected around the joint, chondrolone is injected into the joint, and Miosta Н® is injected into the muscle, and the wound is treated with levomekol ointment. On the 18-19th day, horses normally experience early formation of scabs, lameness, swelling and a local decrease in leg and body temperature, and when treating horses with chronic non-purulent diseases of the joints of the feet, a sharp tickling ointment is used, massage and paraffin applications are applied around the joint and hydrocortisone 0.5% novocaine. It was also reported that with intramuscular injection of 5 ml of Miosta Н® for the first time and 10 days after intra-articular injection of 5 ml of chondrolone, lameness, swelling and local temperature decreased, and body temperature in horses normalized by day 14.